Not a passive learner but an active one: a focus on the efficacy of philosophy-based language instruction and its consequences on EFL learners’ critical thinking, engagement, and academic achievement - Lingxi Li; Sayed M. Ismail; Indrajit Patra; Desta Lami (BMC Psychology, 2024)
Abstract This study investigates the impact of Philosophy-Based Language Teaching (PBLT) on the critical thinking skills and learner engagement of English as a Foreign Language (EFL) students. A concurrent mixed-methods approach, including semi-structured interviews, document analysis, and academic achievement tests, was employed with an experimental group (EG) exposed to PBLT and a control group (CG) receiving traditional instruction. The results reveal a substantial positive effect of PBLT on the critical thinking abilities of EFL learners, as evidenced by thematic analyses of interviews and document content. Themes include heightened critical thinking awareness, collaborative knowledge construction, and increased learner engagement. Academic achievement tests further demonstrate significant improvement in the experimental group’s performance. A comparison with existing literature underscores the novelty of our mixed-methods approach. Implications for language teachers, materials developers, syllabus designers, and policy-makers are discussed, highlighting the potential of PBLT in cultivating critical thinking and learner engagement.